Implementasi Pemenuhan Hak Aksesibilitas Jalur Pemandu bagi Disabilitas Netra di Kota Pekanbaru - Tumorang, Ria Cici; Firdaus, Emilda; Firmanda, Hengki (Faculty of Law, Institut Ilmu Sosial dan Bisnis Andi Sapada., 2023)
Every Indonesian citizen has the same right to get public services provided by the government, including the blind. The blind need special facilities in carrying out their activities in public spaces, such as the accessibility of guide lines/tactile paving. The purpose of this study is to explain the implementation of accessibility rights for the blind in Pekanbaru City. This type of empirical research is used in this study, with a sociological approach, which aims to observe the fulfillment of accessibility rights for blind people in Pekanbaru City. The results found, the provision of tactile paving in Pekanbaru City is still very minimal. It can be concluded that, the implementation of the fulfillment of guideline accessibility rights for persons with visual disabilities in Pekanbaru City has not been carried out properly, and the obstacles to fulfilling guideline accessibility rights in Pekanbaru City are regulatory issues, budgets which result in the unavailability of sidewalks on the roadside. The government of Pekanbaru City should form a regional regulation on persons with disabilities, provide a budget, plan the development of tactile paving, and conduct outreach regarding the importance of fulfilling this. ___ Referensi Buku dengan penulis: Badan Pusat Statistik Kota Pekanbaru. (2022). Kota Pekanbaru Dalam Angka Pekanbaru Municipality in Figures. Pekanbaru: BPS Kota Pekanbaru. Muladi. (2009). Hak Asasi Manusia: Hakekat, Konsep, dan Implikasinya Dalam Perspektif Hukum dan Masyarakat. Bandung: Refika Aditama. Sari, R. O., dan Dewi, D. I. K. (2014). Pemanfaatan Jalur Pemandu Tunanetra pada Pedestrian di Kota Semarang. Semarang: PDIH Undip. Zainuddin. (2018). Metode Penelitian Hukum. Jakarta: Sinar Grafika. Artikel jurnal: Firmanda, H., Firdaus, E., dan Rani, N. P. (2021). Pendampingan Pada Komunitas Anak Disabilitas di Kota Pekanbaru Melalui Pemahaman Hak-Hak Aksessibilitas. Wisanggeni: Jurnal Pengabdian Masyarakat, 40-48. Hasanah, B. (2017). Pelayanan Aksesibilitas Jalan Umum (Jalur Pedestrian) Bagi penyandang Disabilitas (Studi Kasus di Kota Serang). IJTIMAIYA: Journal of Social Science Teaching, 1(1). 60-78. Kahfi, A., Saputra, A. T., Addas, R., dan Rofii, A. A. (2020). “Guiding Block Performance” sebagai Solusi untuk Mengekspresikan Tarian Pakkarena Bagi Perempuan Penyandang Tunanetra di Makassar Sulawesi Selatan. JPAI: Jurnal Perempuan dan Anak Indonesia, 2(2), 31-37. Mapusa, S. G. (2021). Evaluative Review of Government Obligations in Protecting the Right to Work for Persons with Disabilities Through National and Regional Regulations (Ambon City) After the Ratification of the Convention on the Rights of Persons with Disabilities. Balobe Law Journal, 1(2), 57-75. Mizuno, T., Nishidate, A., Tokuda, K., dan Kunijiro, A. R. A. I. (2008). Installation Errors and Corrections in Tactile Ground Surface Indicators in Europe, America, Oceania and Asia. IATSS research, 32(2), 68-80. Ndaumanu, F. (2020). Hak Penyandang Disabilitas: antara Tanggung Jawab dan Pelaksanaan oleh Pemerintah Daerah. Jurnal HAM, 11(1), 131-150. Philona, R., dan Listyaningrum, N. (2021). Implementasi Aksesibilitas bagi Penyandang Disabilitas di Kota Mataram. Jatiswara, 36(1), 38-48. Rahmah, R. (2020). Penerimaan Diri Bagi Penyandang Disabilitas Netra. Alhadharah: Jurnal Ilmu Dakwah, 18(2). 1-16. Rani, N. P., dan Febrina, R. (2021). Hak Aksessibilitas pada Disabilitas di Kota Pekanbaru. Jurnal Ilmu Hukum, 10(1), 57-78. World Wide Web: Tio Tegar Wicaksono. (2018). Tanggung Jawab Negara dalam Rangka Perlindungan dan Pemenuhan Hak Penyandang Disabilitas. https://vivajusticia.law.ugm.ac.id/2018/01/13/tanggung-jawab-negara-dalam-rangka-perlindungan-dan-pemenuhan-hak-penyandang-disabilitas/, Diakses pada tanggal 6 Oktober 2022.